Bioactive nanocomposite for chest-wall replacement: Cellular response in a murine model. (July 2014) - Jungraithmayr, Wolfgang; Laube, Isabelle; Hild, Nora; Stark, Wendelin J; Mihic-Probst, Daniela; Weder, Walter; Buschmann, Johanna
Chest-wall invading malignancies usually necessitate the resection of the respective part of the thoracic wall. Gore-Tex® is the material of choice that is traditionally used to repair thoracic defects. This material is well accepted by the recipient; however, though not rejected, it is an inert material and behaves like a 'foreign body' within the thoracic wall. By contrast, there are materials that have the potential to physiologically integrate into the host, and these materials are currently under in vitro and also in vivo investigation. These materials offer a gradual but complete biodegradation over time, and severe adverse inflammatory responses can be avoided. Here, we present a novel material that is a biodegradable nanocomposite based on poly-lactic- co -glycolic acid and amorphous calcium phosphate nanoparticles in comparison to the traditionally employed Gore-Tex® being the standard for chest-wall replacement. On a mouse model of thoracic wall resection, that resembles the technique and localization applied in humans, poly-lactic- co -glycolic acid and amorphous calcium phosphate nanoparticles and Gore-Tex® were implanted subcutaneously and additionally tested in a separate series as a chest-wall graft. After 1, 2, 4 and 8 weeks cell infiltration into the respective materials, inflammatory reactions as well as neo-vascularization (endothelial cells) were determined in six different zones. While Gore-Tex® allowed for cell infiltration only at the outer surface, electrospun poly-lactic- co -glycolic acid and amorphous calcium phosphate nanoparticles were completely penetrated by infiltrating cells. These cells were composed mainly by macrophages, with only 4% of giant cells and lymphocytes. Total macrophage count increased by time while the number of IL1-β–expressing macrophages decreased, indicating a protective state towards the graft. As such, poly-lactic- co -glycolic acid and amorphous calcium phosphate nanoparticles seem to develop ideal characteristics as a material for chest-wall replacement by (a) having the advantage of full biodegradation, (b) displaying stable chest-wall structures and (c) adapting a physiological and integrating graft compared to Gore-Tex®.